Jurnalisme Kloning di Kalangan Wartawan Kota Surakarta - Kartinawati, Erwin (Jurnal The Messenger, 2017)
News plays role in society. Not only as a source of information but it also can affect people in the cognitive until affective level. Media is not only being the first to present news but also the only one who can present particular news. Unfortunately, for the purpose of fulfilling the target acquisition news, not all of journalists carrying out their profession honestly, presenting news result of the acquisition of its own. Cloning journalism is one of the practices made by some journalists where they do not plunge directly to the process of information gathering, but still get the story. Cloning journalism not just opposite to code of ethics of journalism but also detrimental to media companies concerned. Patterns of cloning journalism carried out in various forms. Regarding the cause are related to the rules of the media company, symbiotic mutualism, and as well as economic motives.